Management of the urban spatial setting to determine the effect of urban heat island on the Bangkok Metropolis, Thailand - S. Chavanavesskul (My University, 2009)
Urbanization and human activities cause higher air temperatures in urban areas than the urban climate.This study uses remote sensing data to observe this urbanization and its surrounding areas.The high temperature can cause problems to the environment, such as high energy consumption on cooling, raised air pollution levels and changes in land use and the creation of a heat island in Bangkok Metropolis, Thailand.This study found that the urban heat island (UHI) problem is caused by the large size of the urban area and sparse vegetation and water resources.Some strategies and approaches are raised in this paper in order to reduce the problem.
Keywords: Urban Heat Island; Urban area; Thermal pollution; Urban Heat Island Mitigation